Learning Innovations to Improve the Pancasila Student Profile in Indonesia - Wahyu Kyestiati Sumarno; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama (Future Science, 2023)
The Pancasila student profile is a number of characteristics and competencies that Indonesian students are expected to achieve. This study aims to examine research on learning innovations that have been carried out by schools in the implementation of the Merdeka Curriculum in the first year in realizing the profile of Pancasila students. The method used in this study is a literature review of scientific journals that have been published on relevant topics. The results of this study provide various learning innovations that have been carried out by various schools that can inspire other schools to realize the Pancasila student profile. It is hoped that this research will provide insight into innovations that need to be carried out for further research.